(untitled) (Journal of the College of Languages (JCL), 2018)
This paper tackles the theme of alienation as being a concurrent state of human being from birth to death; so extensive is the description of this state by writers. Alienation has been a product of their hard experiences and miserable lives. One such writer is Jean-Marie Gustave le Clézio who was so perfect in describing alienation in his works. Upon so many occasions, he imagined one or more of his characters as living in a chaotic world and so lived safely in alienation. The novel "Le Procès-Verbal" is one of the most important of his works. This paper deals with e the narrative structure of novel while shedding light on the hero’s alienation: its essence and causes. The narrative structure is an essential aspect for arriving at the meaning of the novel and its interrelated events. Two aspects are tackled herein: the narrator’s voice and privacy, and the time of narration. The novel Le Procès-Verbalnarrates the story of Adam Polo who chose to live away from social life and as such threw his bicycle into the river and found a shelter in a remote house up at a hill overlooking at the sea. Our man remained there until he found his aim at a remoter place , the asylum. In other words, the novel pictured so perfectly the tragic fate of an educated human being who chose alienation to be the end of his life, and the beginning of oblivion.